DETECTION AND REMOVAL OF SEASONAL AFM1 OCCURRENCE IN VARIOUS MILK SAMPLES COLLECTED FROM DIFFERENT SHOPS OF LAHORE - Muhammad Luqman*1, Amina Arif1, Naseem Zahra2, Usman Wajid*1, Sana Abid1 ., (Chelonian Research Foundation, 2024)
Aflatoxin shows carcinogenic results in hepatocellular carcinoma, mutations and primary immunodeficiency disorders. Aflatoxin M1 is found in milk of animals fed on aflatoxin B1 contaminated food. AFM1 detection is being done by different techniques like thin layer chromatography, high-performance liquid chromatography and enzyme-linked immunosorbent assay, among these ELISA shows more efficacy regarding its diagnosis because it takes short time, small volume of sample is required, and also its budget friendly. The European Union has set range of AFM1 limit as 0.05 ppb in milk while 0.5 ppb limit by the Food and Drug Administration. In this study a total of 100 milk samples were tested, 50 during summer (25 branded and 25 non-branded) and total 50 during winter (25 branded and 25 non-branded), and the results were compared by using IBM SPSS Statistics 28.0 for windows. Results showed that 6% branded milk samples having Mean ± SD of 1.38±0.255 and 16% non-branded milk samples having Mean ± SD of 1.33±0.462 were found beyond the permissible levels of AFM1 as set by FDA. Brand names were kept confidential due to ethical values while ensuring the integrity and generalizability of the research findings. Seasonal variations showed more contamination in winter than summer, both in branded (6% and 0.0%) and non-branded milk samples (20% and 12%). Four lactic acid bacteria isolated from local yoghurt namely; Lactobacillus rhamnosus, Lactobacillus bulgaricus, Lactobacillus plantarum, and Streptococcus thermophilus showed percentage bound aflatoxin M1 of 78.70%, 54.40%, 50.50%, and 37.10% with Mean ± SD of 55.18±0.173 after 24h incubation period. It is essential to test AFB1 contaminated stored feed daily and apply steps and modern methods to remove aflatoxins from food to ensure health fitness without deteriorating the quality and texture of food. Keywords: Aflatoxin B1, aflatoxin M1, enzyme-linked immunosorbent assay, lactic acid bacteria, yoghurt, percentage decontamination.